Phenotypic and Functional Characterization of Long-Term Cryopreserved Human Adipose-derived Stem Cells - Yong, K.W.; Pingguan-Murphy, Belinda; Xu, F.; Wan Abas, Wan Abu Bakar; Choi, J.R.; Omar, Siti Zawiah; Noor Azmi, Mat Adenan; Chua, K.H.; Wan Kamarul Zaman, Wan Safwani (Nature Publishing Group, 2015)
Cryopreservation represents an effective technique to maintain the functional properties of human adipose-derived stem cells (ASCs) and allows pooling of cells via long-term storage for clinical applications, e.g., cell-based therapies. It is crucial to reduce freezing injury during the cryopreservation process by loading the ASCs with the optimum concentration of suitable cryoprotective agents (CPAs). In this study, human ASCs were preserved for 3 months in different combinations of CPAs, including 1) 0.25 M trehalose; 2) 5% dimethylsulfoxide (DMSO); 3) 10% DMSO; 4) 5% DMSO + 20% fetal bovine serum (FBS); 5) 10% DMSO + 20% FBS; 6) 10% DMSO + 90% FBS. Interestingly, even with a reduction of DMSO to 5% and without FBS, cryopreserved ASCs maintained high cell viability comparable with standard cryomedium (10% DMSO + 90% FBS), with normal cell phenotype and proliferation rate. Cryopreserved ASCs also maintained their differentiation capability (e.g., to adipocytes, osteocytes and chondrocytes) and showed an enhanced expression level of stemness markers (e.g., NANOG, OCT-4, SOX-2 and REX-1). Our findings suggest that 5% DMSO without FBS may be an ideal CPA for an efficient long-term cryopreservation of human ASCs. These results aid in establishing standardized xeno-free long-term cryopreservation of human ASCs for clinical applications.